Role of cerebral blood flow autoregulation in internal carotid artery stenosis surgery - V. B. Semeniutin; V. A. Aliev; A. A. Nikiforova; D. V. Svistov; A. V. Savello; G. K. Panuntsev (Вестник хирургии имени И.И. Грекова)
The article presents the data on the dynamics of cerebrovascular reserve indices according to various methods in the perioperative period of reconstructive surgical interventions. We analyzed the relationship between the cerebrovascular reserve and the comorbid factors, the informative value of its indices in predicting ischemic strokes and postoperative hyperperfusion complications.